Effect of Harvest Age and Solvents on the Phenolic Content of Eucheuma cot-tonii Extract - Purbosari, Ninik; Warsiki, Endang; Syamsu, Khaswar; Santoso, Joko (Makara Journal of Science, 2020)
Bioactive compounds in Eucheuma cottonii include phenols or polyphenols with antioxidant, antibacterial, and antiviral properties. Seaweed quality, including phenolic content, is highly determined by several factors, including the growth location, cultivation technique, and harvest age. This study aimed to determine the effect of harvest age and solvent type on the phenolic content of E. cottonii. The effects of harvest age on water content and of simplicia on the extraction process were also determined. Phenolic active ingredients were extracted at three harvest ages (35, 40, and 45 days) and using four solvents (ethanol, ethyl acetate, hexane, and water). Analysis of variance was performed to determine the effects of both factors and their interactions. The older the seaweed, the lesser the water content. The powder produced at all ages is a good simplicia for materials extraction. Results showed that high phenolic content was obtained from the E. cottonii extract at the age of 35 days with ethyl acetate as the solvent.